2021
DOI: 10.3390/jnt2030010
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Gold Nanorod Biocompatibility with Sodium Dodecyl Sulfate Stabilization

Abstract: Due to their well-defined plasmonic properties, gold nanorods (GNRs) can be fabricated with optimal light absorption in the near-infrared region of the electromagnetic spectrum, which make them suitable for cancer-related theranostic applications. However, their controversial safety profile, as a result of surfactant stabilization during synthesis, limits their clinical translation. We report a facile method to improve GNR biocompatibility through the presence of sodium dodecyl sulfate (SDS). GNRs (120 × 40 nm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Evaluating the tumoral distribution of a drug or particle-drug conjugate is an important variable that is often neglected, as most drugs are assumed to distribute homogeneously into a tumor [ 22 ]. In previous studies, we demonstrate that GNP cellular uptake [ 23 , 24 ], as well as intratumoral distribution and retention [ 25 , 26 ], is strongly influenced by surface chemistry. We have shown that when GNPs are surface passivated with a bovine serum albumin (BSA) protein layer, internalization of the particles into cancer cells occurs through larger vesicle formation with reduced gold content per cell, and when injected intratumorally in a murine lung cancer model, the BSA passivated particles diffuse more overtime throughout the tumor tissue [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the tumoral distribution of a drug or particle-drug conjugate is an important variable that is often neglected, as most drugs are assumed to distribute homogeneously into a tumor [ 22 ]. In previous studies, we demonstrate that GNP cellular uptake [ 23 , 24 ], as well as intratumoral distribution and retention [ 25 , 26 ], is strongly influenced by surface chemistry. We have shown that when GNPs are surface passivated with a bovine serum albumin (BSA) protein layer, internalization of the particles into cancer cells occurs through larger vesicle formation with reduced gold content per cell, and when injected intratumorally in a murine lung cancer model, the BSA passivated particles diffuse more overtime throughout the tumor tissue [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the tumoral distribution of a drug or particle-drug conjugate is an important variable that is often neglected, as most drugs are assumed to distribute homogeneously into a tumor [19]. In previous studies, we demonstrate that GNP cellular uptake [20,21], as well as intratumoral distribution and retention [22,23], is strongly influenced by surface chemistry. We have shown that when GNPs are surface passivated with a bovine serum albumin (BSA) protein layer, internalization of the particles into cancer cells occurs through larger vesicle formation with reduced gold content per cell, and when injected intratumorally in a murine lung cancer model, the BSA passivated particles diffuse more overtime throughout the tumor tissue [22].…”
Section: Introductionmentioning
confidence: 85%
“…The precipitated AuNRs were redispersed in 5 mL of deionized water for further use. For cell culture samples, the cytotoxicity of AuNRs caused by CTAB was reduced by using SDS as an overcoating agent to stabilize the AuNR surface . The AuNR solution was precipitated, and the AuNR particles were resuspended in SDS solution at 10 mM.…”
Section: Methodsmentioning
confidence: 99%